2020
DOI: 10.3389/fpsyt.2019.00960
|View full text |Cite
|
Sign up to set email alerts
|

Bullying History and Mental Health In University Students: The Mediator Roles of Social Support, Personal Resilience, and Self-Efficacy

Abstract: differences found between an individualistic country and a collectivistic country have important implications for understanding and planning interventions to reduce bullying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 50 publications
3
32
0
2
Order By: Relevance
“…In this large, population-based, cross-sectional study, we found that exposure to intrafamilial aggression or peer bullying during childhood was associated with adult risk of depression in China, and peer bullying had a closer association with life-course depression, with a similar effect size of having a chronic disease. Our results are similar to those of previous studies in western countries 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 20 , 33 , 34 , 35 that have found a negative association between childhood adverse experience and adult mental health, despite culture differences. This study adds to the emerging evidence that sibling aggression, a less-studied type of intrafamilial aggression, was also associated with depression symptoms in adulthood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this large, population-based, cross-sectional study, we found that exposure to intrafamilial aggression or peer bullying during childhood was associated with adult risk of depression in China, and peer bullying had a closer association with life-course depression, with a similar effect size of having a chronic disease. Our results are similar to those of previous studies in western countries 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 20 , 33 , 34 , 35 that have found a negative association between childhood adverse experience and adult mental health, despite culture differences. This study adds to the emerging evidence that sibling aggression, a less-studied type of intrafamilial aggression, was also associated with depression symptoms in adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…Intrafamilial aggression and peer bullying in childhood are recognized as major social issues worldwide, conferring considerable risk for life-course mental health problems. 1 , 2 , 3 A growing number of studies 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 have established a robust association between earlier-life exposure to adverse experience (eg, parental physical maltreatment, sibling aggression, or peer bullying) and later-life psychological outcomes, such as anxiety, depression, self-harm, and attempt or completion of suicide. Although our knowledge of the consequences of adverse experiences is primarily based on studies performed in highly industrialized countries with societies considered to be individualistic, such as North America, Europe, and Australia, similar associations began to be found in more collectivistic or Confucian cultures, such as China, where harsh parenting (eg, “spare the rod and spoil the child”) and sibling hierarchical relationships (eg, older siblings get greater respect, but also take on the responsibility of providing care for younger siblings) are standard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that resilience plays a role in the underlying mechanism of these relationships. These results are consistent with previous research (e.g., Kabadayi & Sari, 2018;Lin et al, 2020;Moore & Woodcock, 2017). The relationship between bullying experiences and resilience may perhaps be related to target self-perceptions after being bullied.…”
Section: The Role Of Resiliencesupporting
confidence: 92%
“…Employing these character strengths increases happiness [ 20 ] and enhances positive feelings resulting in a greater overall sense of well-being [ 19 ]. Further, these characteristics enhance positive relationships with patients, improve clinical outcomes [ 19 ] and are associated with well-being, stress coping, low rate of burnout, a reduced sense of victimization and improvements in medical students’ mental health [ 21 , 22 , 23 , 24 , 25 ]. Moreover, feeling supported by family members, friends or significant others helps to reduce stress and mental problems and enhances positive mental health and self-esteem [ 26 ].…”
Section: Introductionmentioning
confidence: 99%